Communication Strategy In Delivering Semester Credit System (SKS) Programs With Students At State Islamic Junior High School (Mtsn )Of 01 Medan City - Agustina Muliati; M. Joharis Lubis; Nathanael Sitanggang (International Journal of Educational Research & Social Sciences, 2021)
The aimed of this study was to determine the appropriate communication strategy in the delivery of the Semester Credit System program at MTsN 1 Medan. This is because there are still many students who do not understand the SKS program they are currently undergoing. The formulation of the problem in this study is how the strategy used in delivering the credit program at MTsN 1 Medan. The methodology used with a qualitative approach is by collecting data through in-depth interviews, observation, documentation, and conducting a literature review obtained from books, journals, seminar results and other scientific works relevant to the theme of communication strategy research. From the results of the study, it was found that there were communication strategies used, among others, by using redundancy, canalizing, informative, persuasive, educative, cursive methods, selecting communication media and using Dornyei taxonomy, namely the use of assistance. And as the results of this study, it can be concluded that the communication strategy in delivering the SKS program is effective as evidenced by a significant increase in students' understanding of the SKS program after the communication strategy is implemented.